Development and short evaluation of the Dutch healthy diet index for pregnant women; DHD-P - Faessen, Janine P. M.; Feskens, Edith J. M.; Brouwer-Brolsma, Elske M. (Frontiers in Nutrition, 2024)
Introduction Diet quality indices provide a quick indicator of overall diet and are commonly used in research and surveillance. We developed a Dutch Healthy Diet for pregnant women (DHD-P) index, comprising 22 components aligned with the 2021 Dutch food-based dietary guidelines for pregnant women. Our evaluation focused on assessing its performance and sensitivity to change. Methods The DHD-P index was quantified by using a validated Food Frequency Questionnaire (FFQ) and two 24-h recalls at 12 and 24 weeks gestation completed by 24-to-41 year old pregnant women participating in the GLIMP-II study. Strength and direction of associations were evaluated based on de-attenuated correlation coefficients between FFQ and 24-h recall data at 24 weeks gestation (n = 47). Sensitivity to change was evaluated by comparing DHD-P index data assessed by both FFQ and recalls at 12 and 24 weeks gestation using paired t-tests or Wilcoxon Signed Rank Test (n = 27). Results De-attenuated correlation coefficients between FFQ and 24-recall data showed a good correlation for the total DHD-P score (rho = 0.57) and moderate to good correlations for component scores. FFQ as well as recall data showed comparable dietary intake at 12 and 24 weeks, suggesting minimal changes during pregnancy. Correlations over time were moderate-to-good for scores based on FFQ and low to moderate for scores based on 24hRs, indicating better reproducibility of scores based on FFQ data. Conclusion Considering the moderate to good correlations, the DHD-P index appears to be an appropriate index to assess diet quality among pregnant women, and could serve as a foundation to provide dietary feedback toward healthier food choices. Studies including dietary data for all relevant food groups and nutrients are needed to substantiate our findings and further explore the DHD-P sensitivity to change.